Severe hypernatremic dehydration associated with cerebral venous and aortic thrombosis in the neonatal period. (19th January 2012) - Hbibi, Mohammed; Abourazzak, Sana; Babakhouya, Abdeladim; Boubou, Meryem; Atmani, Samir; Tizniti, Siham; Bouharrou, Abdelhak
Abstract : Severe neonatal hypernatremia is an important electrolyte disorder that has serious effects. Cerebral venous thrombosis and aortic thrombosis are relatively rare in severe neonatal hypernatremic dehydration. The authors report a case of cerebral venous thrombosis, associated with aortic thrombosis revealed by dehydration in a 9-day-old boy. Diagnostic was performed using Doppler ultrasound and imaging techniques. Thrombosis was resolved after anticoagulation treatment with low-molecular weight heparin for 1 month, and then was substituted by oral anticoagulant. The case report is followed by a review of the literature dealing with clinical, aetiological and therapeutic aspects of neonatal thrombosis.